Rosuvastatin Is Effective to Decrease CD8 T-Cell Activation Only in HIV-Infected Patients With High Residual T-Cell Activation Under Antiretroviral Therapy. (1st April 2016) - Weiss, Laurence; Chevalier, Mathieu F.; Assoumou, Lambert; Paul, Jean-Louis; Alhenc-Gelas, Martine; Didier, Céline; Taibi, Saïd; Manea, Elena-Maria; Campa, Pauline; Girard, Pierre-Marie; Costagliola, Dominique
Abstract : Objective: The aim of the trial was to evaluate in patients under antiretroviral therapy (ART) the effect of rosuvastatin on cellular and soluble markers of immune activation/inflammation, as well as to identify patients who better benefit from statin administration. Methods: IMEA-043-CESAR was a phase II open-label pilot trial that enrolled patients under suppressive ART and CD4 <500/mm 3 . Patients received rosuvastatin (20 mg/d) for 12 weeks. The primary outcome was the variation at week 12 (W12) in the proportion of CD38 + HLA-DR + CD8 + T lymphocytes. Secondary outcomes included evolution of other markers of T-cell activation and of inflammatory biomarkers between baseline, W12, and W24. Results: Fifty patients were enrolled; end points were available for 43 patients. When considering all patients, the proportion of CD38 + HLA-DR + CD8 + T cells did not significantly decline throughout the follow-up. However, the proportion of CD38 + CD8 + T cells significantly decreased at W12 [median percentage change of −22.2% (−32.3; +1.4)]. Principal component analysis allowed identification of 3 groups of patients based on their baseline activation/inflammation profiles, 1 group with elevated levels of CD8 T-cell activation, and a small group with high levels of systemic inflammation and low levels of T-cell activation. Half of the patients exhibited relatively low levels of inflammation and activation. The proportion of activated CD8 T cells significantly decreased only in the particular group of patients with high baseline CD8 T-cell activation. Conclusions: This study shows that combining rosuvastatin with effective ART can result in a sustained decrease in CD8 T-cell activation and highlights the importance of identifying patients who can benefit from specific immunotherapeutic strategies.